A statistical correlation between virulence genes and clinical features among patients with shigellosis in Mirzapur, Bangladesh - Chowdhury, Dr. Visnu Pritom (BRAC University, 2017)
A Dissertation Submitted in Partial Fulfillment of the Requirements’ for the Degree of Master of Science in Biotechnology 2016.